2006
DOI: 10.1002/ana.20798
|View full text |Cite
|
Sign up to set email alerts
|

A novel role of phospholipase A2 in mediating spinal cord secondary injury

Abstract: PLA2, increased significantly after SCI, may play a key role in mediating neuronal death and oligodendrocyte demyelination following SCI. Blocking PLA2 action may represent a novel repair strategy to reduce tissue damage and increase function after SCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
149
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 147 publications
(155 citation statements)
references
References 42 publications
6
149
0
Order By: Relevance
“…cPLA 2 is an 85kDa protein enzyme that preferentially produces arachidonic acid (AA) by hydrolyzing the sn-2 position of glycerophospholipids [49]. Our lab has previously shown that cPLA 2 activation increased as early as 8 hours and peaked at 7 days post-SCI [22,21]. Activation of cPLA 2 by its activator, ceramide-1-phosphate or A23187, is sufficient to induce neuronal death, whereas cPLA 2 inhibition reduces cell loss in vitro [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…cPLA 2 is an 85kDa protein enzyme that preferentially produces arachidonic acid (AA) by hydrolyzing the sn-2 position of glycerophospholipids [49]. Our lab has previously shown that cPLA 2 activation increased as early as 8 hours and peaked at 7 days post-SCI [22,21]. Activation of cPLA 2 by its activator, ceramide-1-phosphate or A23187, is sufficient to induce neuronal death, whereas cPLA 2 inhibition reduces cell loss in vitro [22].…”
Section: Discussionmentioning
confidence: 99%
“…Our prior research has demonstrated significant increases of PLA 2 activity and cPLA 2 expression following SCI [21,22]. cPLA 2 is highly expressed in neurons, axons and glial cells and peaked at day 1 in axons, day 3 in glial cells, and day 7 in neurons after SCI [21]. Activation of cPLA 2 is sufficient to induce spinal cord neuronal death in vitro.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Injection of phospholipase A 2 has also been shown to initiate inflammation and cell tissue damage that are characteristic of traumatic SCI. 47 Chemical models of demyelination are useful for evaluation of therapies directed to enhance remyelination. These models include injection of ethidium bromide, lysolethicin, murine hepatitis virus, or a cocktail of myelin-specific antibodies and complement.…”
Section: Chemical Modelsmentioning
confidence: 99%
“…5,6 All those techniques can be used to observe morphology changes of various types of cells or structures in the WM at the cellular level. However, the requirement of the staining procedure may cause false outcomes 7,8 .…”
mentioning
confidence: 99%